Debate About “Dezemberfieber” — Reply and Response - Gunnar Schwarting; Christoph Siemroth (Wirtschaftsdienst)
Abstract In its June 2022 issue, Wirtschaftsdienst published an article by Christoph Siemroth entitled “Dezemberfieber senken: Vermeidung von verschwenderischen Jahresendausgaben”. Now, Gunnar Schwarting takes a different view in his reply to the article that is followed by a response of Christoph Siemroth explaining his position.